Nano-casting and doping double-strategy improved lanthanum-manganese perovskite catalyst, preparation method thereof and application of catalyst in degradation of halogenated organic pollutants
Through the dual strategy of nanocasting and doping, the lanthanum manganese perovskite catalyst was improved, and the problem of poor results in the existing catalysts in dealing with difficult-to-degrade halogenated organic pollutants was solved, achieving high-efficiency deep degradation and low energy consumption catalytic effects.
Patent Information
- Application Number
- CN202411549536.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-07
AI Technical Summary
Existing catalysts have limited effects when dealing with difficult-to-degrade halogenated organic pollutants, and their catalytic activity is prone to decline, which limits the practical application efficiency of thermal catalytic technology.
The lanthanum manganese perovskite catalyst is improved by using nanocasting and doping dual strategies. The morphology and structure of the catalyst are optimized through nanocasting technology, the specific surface area and oxygen adsorption capacity are increased, and the electronic structure is adjusted through element doping, increasing the active site and Electronic transfer capability.
It significantly improves the redox capacity and catalytic effect of the catalyst, achieves efficient deep degradation of halogenated organic pollutants, reduces the generation of gas by-products, and improves the performance of completely oxidizing pollutants into carbon dioxide.
Smart Images

Figure CN119386890A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of organic pollutant treatment and nanomaterial preparation, and in particular to a catalyst, a preparation method and application thereof, and more specifically to a nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst, a preparation method thereof and application thereof in the degradation of halogenated organic pollutants. Background Art
[0002] Halogenated organic pollutants, as a class of organic compounds containing halogen atoms, are widely used in the fields of pesticides, dyes and flame retardants. However, halogenated organic pollutants are highly persistent and difficult to biodegrade, which leads to their widespread presence in the environment, posing a serious threat to ecology and human health.
[0003] At present, the treatment technologies for halogenated organic pollutants mainly include adsorption, combustion, biological and photocatalytic methods, but these technologies have limitations, such as high cost, high energy consumption, long reaction cycle and many degradation by-products. In contrast, thermal catalytic technology uses catalysts to achieve oxidative decomposition of halogenated organic pollutants at lower temperatures, which has the advantages of reducing energy consumption and treatment costs, and can treat a variety of halogenated organic pollutants. However, when using thermal catalytic technology to treat difficult-to-degrade halogenated organic matter, ordinary catalysts have limited effects, and their activity is easily reduced during the catalytic process, which limits their practical application effectiveness.
[0004] Therefore, further research is still needed on the catalysts used to treat halogenated organic matter to overcome the current problems. Summary of the invention
[0005] In view of this, the main purpose of the present disclosure is to provide a nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst and its preparation method and application in the degradation of halogenated organic pollutants, in order to at least partially solve at least one of the above-mentioned technical problems.
[0006] To achieve the above purpose, the technical solution of the present invention is as follows:
[0007] In one aspect of the present disclosure, a method for preparing a nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst is provided, comprising:
[0008] Using transition metal salt as dopant, mixing transition metal salt, lanthanum salt, manganese salt and complexing agent in a solvent to form a mixed solution;
[0009] Adding nano-silicon dioxide to the mixed solution, stirring and heating to a gel state, and then drying to obtain a solid precursor;
[0010] The solid precursor is calcined to obtain a calcined product, wherein the calcined product includes nano-silicon dioxide and transition metal-doped lanthanum manganese perovskite;
[0011] The calcined product is added into an alkaline solution, and the nano-silicon dioxide is etched and removed to form a nano-pore structure, thereby obtaining a nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst.
[0012] In another aspect of the present disclosure, a nano-casting and doping dual strategy for improving lanthanum manganese perovskite catalyst is provided.
[0013] In another aspect of the present disclosure, there is provided an application of the above-mentioned nanocasting and doping dual strategy improved lanthanum manganese perovskite catalyst in the degradation of halogenated organic pollutants.
[0014] According to an embodiment of the present disclosure, a method for preparing a nanocasting and doping dual-strategy improved lanthanum manganese perovskite catalyst is provided, which combines the two strategies of nanocasting technology and element doping. On the one hand, the morphology and structure of the perovskite catalyst are optimized by nanocasting technology, thereby increasing the specific surface area and oxygen adsorption capacity of the perovskite catalyst. On the other hand, the electronic structure of the catalyst is adjusted by element doping, the number of active sites is increased, and the transfer of electrons and the activation of oxygen are promoted, making it easier for oxygen to be converted into active oxygen. The synergistic effect of the two strategies promotes a complete oxidation path, thereby significantly improving the redox ability of the perovskite catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1a This is a scanning electron microscope image of the lanthanum manganese perovskite catalyst improved by the dual strategy of nanocasting and doping in Example 1 of the present disclosure;
[0016] Figure 1b This is a scanning electron microscope elemental mapping diagram of the lanthanum manganese perovskite catalyst improved by the dual strategy of nanocasting and doping in Example 1 of the present disclosure;
[0017] Figure 2a This is a scanning electron microscope image of the non-modified lanthanum manganese perovskite catalyst in Comparative Example 1 of the present disclosure;
[0018] Figure 2b This is a scanning electron microscope image of the lanthanum manganese perovskite catalyst improved by doping with a single strategy in Comparative Example 2 of the present disclosure;
[0019] Figure 2c This is a scanning electron microscope image of the lanthanum manganese perovskite catalyst improved by the nanocasting single strategy in Comparative Example 3 of the present disclosure;
[0020] Figure 3 X-ray diffraction patterns of the catalysts in Example 1 and Comparative Examples 1 to 3 of the present disclosure;
[0021] Figure 41 is a comparison chart of hydrogen reduction temperature and consumption of the catalysts in Example 1 of the present disclosure and Comparative Examples 1 to 3, wherein a is a chart of hydrogen consumption of the catalysts in Example 1 of the present disclosure and Comparative Examples 1 to 3 as a function of temperature; b is a comparison chart of total hydrogen consumption of the catalysts in Example 1 of the present disclosure and Comparative Examples 1 to 3 before and after 600° C.;
[0022] Figure 5 It is a quantitative distribution diagram of degradation products during the degradation of hexachlorobutadiene by the catalyst in Example 1 and Comparative Examples 1 to 3 of the present disclosure;
[0023] Figure 6 It is a comparison chart of the carbon dioxide production produced by thermal catalytic oxidation of hexachlorobutadiene by the catalysts in Example 1 of the present disclosure and Comparative Examples 1 to 3 under the same reaction conditions. DETAILED DESCRIPTION
[0024] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in conjunction with specific embodiments.
[0025] The endpoints and any values of the ranges disclosed in this disclosure are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this disclosure.
[0026] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0027] Halogenated organic compounds are ubiquitous due to their wide application in industry and daily life. However, the high stability and difficult-to-degrade properties of these compounds lead to their persistent presence in the environment, posing a significant risk to ecosystems and human health. Currently, adsorption, combustion, biological treatment and photocatalysis are mainly used to treat these pollutants, but these methods are often costly, have long treatment cycles, and may produce harmful byproducts. As an alternative, thermal catalysis can decompose halogenated organic pollutants at lower temperatures, thereby reducing energy consumption and treatment costs, and can treat a variety of types of halogenated organic pollutants. However, when faced with difficult-to-degrade halogenated organics, thermal catalysis may be limited due to insufficient catalyst activity, thus affecting its efficiency in practical applications. Therefore, in order to improve the efficiency and effectiveness of thermal catalysis in degrading halogenated organic compounds, the development and optimization of catalysts has become the key to improving the performance of thermal catalysis.
[0028] Lanthanum manganese perovskite (LaMnO3) has been widely used in the catalytic degradation of volatile organic compounds as an economical and thermally stable non-precious metal catalyst. However, when it is used to treat refractory halogenated organic pollutants, it may lead to poor catalytic oxidation effect and incomplete degradation due to its low specific surface area and electron transfer capacity. Therefore, it has become an urgent problem to improve the lanthanum manganese perovskite catalyst to improve its catalytic performance in treating refractory halogenated organic pollutants.
[0029] In the process of realizing the concept of the present disclosure, it was found that the nanocasting method can effectively synthesize non-siliceous mesoporous materials with high specific surface area, thereby significantly improving the specific surface area and adsorption capacity of the material. In addition, by utilizing the flexibility of element regulation of perovskite materials, element doping can change the electronic configuration, increase active sites, thereby improving the electron transfer ability and promoting the activation of surface adsorbed oxygen. However, in the redox cycle of the catalytic reaction, a single enhanced oxygen adsorption or activation cannot promote the complete oxidation path, resulting in limited improvement in the redox ability and catalytic effect of the catalyst. Therefore, a control method combining the nanocasting method and the element doping strategy is adopted. In the process of catalyst catalytic oxidation, by simultaneously enhancing the adsorption and activation of oxygen to promote the complete oxidation path, a synergistic effect of "1+1>2" is achieved, thereby significantly improving the effect of catalyst catalytic oxidation and achieving efficient deep degradation of halogenated organic pollutants.
[0030] According to an embodiment of one aspect of the present disclosure, a method for preparing a nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst is proposed, comprising:
[0031] Using transition metal salt as dopant, mixing transition metal salt, lanthanum salt, manganese salt and complexing agent in a solvent to form a mixed solution;
[0032] Adding nano-silicon dioxide to the mixed solution, stirring and heating to a gel state, and then drying to obtain a solid precursor;
[0033] The solid precursor is calcined to obtain a calcined product, wherein the calcined product includes nano-silicon dioxide and transition metal-doped lanthanum manganese perovskite;
[0034] The calcined product is added into an alkaline solution, and the nano-silicon dioxide is etched and removed to form a nano-pore structure, thereby obtaining a perovskite catalyst.
[0035] According to the embodiments of the present disclosure, a method for preparing a nanocasting and doping dual-strategy improved lanthanum manganese perovskite catalyst is proposed. On the basis of preparing the perovskite catalyst by the sol-gel method, the two strategies of nanocasting technology and element doping are combined. On the one hand, the morphology and structure of the catalyst are improved by nanocasting technology, which significantly increases the pore volume and specific surface area of the catalyst, so that the catalyst can more effectively capture and retain oxygen and pollutants, thereby improving its oxidation capacity. On the other hand, by doping other low-valent transition metal elements in the perovskite structure, the electronic structure of the catalyst is changed, the catalytic active sites are further increased, and the transfer of electrons and the activation of oxygen are promoted, so that the oxygen adsorbed on the surface can more easily obtain electrons and be activated into active oxygen, thereby further improving the catalytic activity of the catalyst. The synergistic effect of the two strategies promotes a complete oxidation path, achieving an effect beyond a single strategy, that is, a synergistic effect of "1+1>2", which significantly enhances the redox ability of the catalyst.
[0036] According to the embodiments of the present disclosure, the transition metal salt, lanthanum salt, and manganese salt are soluble salts selected from any one of nitrates, sulfates, and citrates. The soluble salts are easily soluble in water to form a uniform ion solution, which is beneficial to achieve uniform distribution of ions during the preparation of the perovskite catalyst, thereby obtaining a catalyst with uniform performance.
[0037] Among them, the transition metal is selected from any one of iron, cobalt, nickel and copper. The low-cost transition metal replaces the manganese in the lanthanum manganese perovskite in an appropriate amount, which can effectively increase the active sites, improve the electron exchange capacity, promote oxygen activation, and enhance the redox property of the catalyst. For example, the transition metal salt can be nickel nitrate, iron nitrate, cobalt nitrate, copper nitrate, nickel sulfate, cobalt sulfate, nickel citrate, copper citrate, etc.; the lanthanum salt can be lanthanum nitrate, lanthanum sulfate, lanthanum citrate, etc.; the manganese salt can be manganese nitrate, manganese sulfate, manganese citrate, etc.
[0038] The complexing agent is selected from organic acids, preferably any one of citric acid, ethylenediaminetetraacetic acid, and lactic acid. The above organic acids have strong complexing ability and can form stable complexes with metal ions, which helps to slow down the combination of metal ions and anions and maintain the activity and stability of metal ions in the solution. The solvent is a mixed solution of ethanol and water, wherein the proportion of ethanol is 0-1, preferably 0.6-0.8.
[0039] The molar ratio of lanthanum salt, manganese salt, transition metal salt and complexing agent is 1: (1-x): x: 2, wherein x ranges from 0 to 1, for example, x can be 0, 0.1, 0.3, 0.5, 0.7, 0.9, etc. Transition metal doping can change the internal electronic structure of perovskite, increase electron transfer sites, and promote oxygen activation ability and redox properties. The range of transition metal salt x is preferably 0.2 to 0.4, for example, x can be 0.2, 0.3, 0.4, etc. Within this range, the doping ratio of transition metal can ensure the performance of the catalyst while avoiding unnecessary cost increase caused by excessive use of transition metal, taking into account cost-effectiveness.
[0040] According to the embodiments of the present disclosure, the particle size of nano-silicon dioxide is less than 300 nm, for example, it can be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, etc. As a pore-forming agent, nano-silicon dioxide has the characteristics of small diameter, high temperature resistance and easy etching. In the preparation process of perovskite oxide, nano-silicon dioxide can accompany it through the high-temperature calcination stage and leave abundant pores after the subsequent etching step. These pores expand the specific surface area of the catalyst, thereby enhancing the oxygen adsorption capacity of the catalyst surface and improving its redox performance. The molar ratio of the amount of nano-silicon dioxide added to the theoretical yield of perovskite is 1:2~1:1, for example, it can be 1:2, 1:1.8, 1:1.5, 1:1.3, 1:1, etc. This ratio can ensure that sufficient nano-silicon dioxide is provided to give full play to its pore-forming effect, thereby maximizing the specific surface area and performance of the catalyst. In addition, it avoids the interference of excessive nano-silicon dioxide on the crystal structure of perovskite, which in turn has an adverse effect on its overall performance.
[0041] According to an embodiment of the present disclosure, nano-silica is added to the mixed solution, stirred and heated to a gel state, and the nano-silica particles are evenly distributed in the solution by stirring. The heating temperature is 80-95°C, for example, 80°C, 85°C, 90°C, 95°C, etc. Within this temperature range, it is ensured that the metal salt and the complexing agent react fully to form a stable gel structure. Then drying is performed to remove the solvent (a mixed solution of ethanol and water) therein to obtain a solid precursor, and the drying temperature is 80-120°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, etc. This temperature range can effectively remove the solvent while avoiding structural changes or decomposition of the solid precursor.
[0042] According to an embodiment of the present disclosure, the calcination treatment includes: first heating the solid precursor to a first calcination temperature of 200-300°C, such as 200°C, 220°C, 250°C, 270°C, 300°C, etc., the first heating rate is 1-3°C / min, such as 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, etc., and the heat preservation reaction is carried out for 1-2 hours, such as 1 hour, 1.2 hours, 1.5 hours, 1.7 hours, 2 hours, etc. The organic matter and residual solvent in the precursor are removed by low-temperature calcination, and the initial chemical bond formation and phase transition are promoted. Then continue to heat up to the second calcination temperature for calcination, the second calcination temperature is 700-800°C, for example, it can be 700°C, 720°C, 740°C, 760°C, 780°C, 800°C, etc., through the second high temperature calcination to promote the formation of perovskite structure and crystal growth. The second heating rate is 1-3°C / min, for example, it can be 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, etc., and the calcination time is 1-2 h, for example, it can be 1 h, 1.2 h, 1.5 h, 1.7 h, 2 h, etc., which can ensure that the material has enough time for lattice rearrangement and phase change to form the desired perovskite structure and obtain a calcined product.
[0043] According to an embodiment of the present disclosure, the alkaline solution is selected from any one of a sodium hydroxide solution or a potassium hydroxide solution, and the concentration of the alkaline solution is 1 to 3 mol / L, for example, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, etc. The alkaline solution is used to etch and remove the nano-silicon dioxide, and the number of etchings is 3 to 5 times, for example, 3 times, 4 times, and 5 times, and the etching time is 2 to 4 hours each time, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, etc. The alkaline solution can effectively react with silicon dioxide, through the following reaction formula:
[0044] SiO2+ 2OH - → SiO3 2- + H2O
[0045] This achieves the removal of the pore-forming agent nano-silica, and the catalyst is left with abundant pores after etching, which significantly increases the specific surface area of the catalyst and improves the oxygen adsorption capacity and redox properties of the catalyst surface.
[0046] According to an embodiment of another aspect of the present disclosure, a nano-casting and doping dual strategy improved lanthanum manganese perovskite catalyst having a nano-pore structure and transition metal doping is provided.
[0047] According to the embodiments of the present disclosure, the transition metal-doped nanocasting and doping dual-strategy improved lanthanum manganese perovskite catalyst has a rich nanopore structure, and its micromorphology presents a nano honeycomb structure with a wall thickness of 5 to 15 nm and a pore radius of 10 to 50 nm, which not only increases the specific surface area of the catalyst, but also provides more adsorption sites for oxygen and pollutants, thereby enhancing the contact between the catalyst and the reactants, which is beneficial to improving the efficiency of the catalytic reaction. In addition, through the doping of transition metals, the electronic configuration of the catalyst is changed, and the number of active sites is increased, thereby improving the electron transfer ability, making it easier for oxygen to obtain electrons and convert into active oxygen, and promoting the activation of surface adsorbed oxygen. The synergistic effect of the nanopore structure and element doping promotes a complete oxidation path and further enhances the redox ability of the catalyst.
[0048] According to an embodiment of another aspect of the present disclosure, there is provided an application of the above-mentioned nano-casting and doping dual strategy improved lanthanum manganese perovskite catalyst in the degradation of halogenated organic pollutants.
[0049] According to the embodiments of the present disclosure, the perovskite catalyst prepared by the two strategies of nanocasting technology and element doping has a synergistic effect to form a complete oxidation path improvement, which can achieve a higher redox capacity. When degrading halogenated organic pollutants, the improved lanthanum manganese perovskite catalyst using the dual strategy of nanocasting and doping can not only achieve a more efficient and deeper degradation effect, but also reduce the generation of gaseous by-products, while improving the performance of completely oxidizing pollutants to carbon dioxide.
[0050] According to an embodiment of the present disclosure, the degradation method includes:
[0051] The nanocasting and doping dual-strategy improved lanthanum manganese perovskite catalyst and halogenated organic pollutants were placed in a reactor, and then an empty body was introduced, and the humidity of the air was controlled to be 0~20%. The appropriate humidity simulates the humidity level of industrial exhaust or other pollutants in reality, thereby increasing the guarantee for the practical application of the catalyst. At the same time, the air flow rate was controlled to be 20~100 ml / min. The appropriate flow rate range can ensure that there is enough contact time between the air and the catalyst, so that oxygen and pollutants can be effectively transferred to the catalyst surface, while avoiding the reactants being taken away without sufficient reaction due to excessive flow rate. Under heating conditions of 200~350℃, the halogenated organic pollutants were degraded using the nanocasting and doping dual-strategy improved lanthanum manganese perovskite catalyst, which can activate the active sites in the catalyst in a lower temperature range, so that the catalyst can effectively promote the degradation reaction of halogenated organic pollutants. At the same time, the mild reaction conditions also significantly reduced energy consumption, making the perovskite catalyst show good application potential in environmental governance.
[0052] According to an embodiment of the present disclosure, the halogenated organic pollutant includes any one of hexachlorobutadiene, hexachlorobenzene, and chloroform.
[0053] In order to make the purpose, technical scheme and advantages of the present disclosure clearer, the present disclosure is further described in detail below in conjunction with specific examples and drawings. Specific techniques or conditions not specified in the examples are all conventional methods, which can be carried out according to the techniques or conditions described in the literature in the field or according to the product instructions. It should be noted that the methods provided in the present disclosure are all conventional methods unless otherwise specified, and the reactants and reagents can be obtained from public commercial channels unless otherwise specified.
[0054] Embodiment 1:
[0055] This embodiment 1 provides a nano-casting and doping dual strategy to improve the lanthanum manganese perovskite catalyst (LaMn 0.7 Ni 0.3 The preparation method of O3-Nano) is as follows:
[0056] Using nickel nitrate as a dopant, lanthanum nitrate, manganese nitrate, nickel nitrate and citric acid in a molar ratio of 1:0.7:0.3:2 are mixed in a 3:1 mixture of ethanol and water to form a mixed solution;
[0057] Add nano-silicon dioxide to the mixed solution, the mass ratio of nano-silicon dioxide dosage to the theoretical yield of perovskite is 1:1, heat and stir at 80°C until it reaches a gel state, and then dry at 100°C for 6 hours to obtain a solid precursor;
[0058] The solid precursor is calcined, the solid precursor is heated from room temperature to 300°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then continued to be heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2 hours to obtain a calcined product, the calcined product comprising nano-silicon dioxide and nickel-doped lanthanum manganese perovskite;
[0059] The calcined product was added to a 2 mol / L sodium hydroxide solution to etch away the nano-silicon dioxide to form a nano-pore structure. The etching times were 3 times, and each etching time was 3 h. Then, the product was centrifuged and washed 5 times with deionized water, and dried at 80 ° C for 12 h to obtain the nano-casting and doping dual strategy improved lanthanum manganese perovskite catalyst LaMn 0.7 Ni 0.3 O3-Nano.
[0060] Figure 1a This is a scanning electron microscope image of the lanthanum manganese perovskite catalyst improved by the dual strategy of nanocasting and doping in Example 1 of the present disclosure.
[0061] Figure 1b This is a scanning electron microscope elemental mapping image of the lanthanum manganese perovskite catalyst improved by the dual strategy of nanocasting and doping in Example 1 of the present disclosure.
[0062] like Figure 1a As shown in the figure, the nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst prepared in Example 1 presents a nano honeycomb structure with a wall thickness of 5-15 nm and a pore radius of 10-50 nm. The pore structure is rich and obvious, which makes the perovskite catalyst have a larger specific surface area and better adsorption capacity. Figure 1b As shown, nickel element is uniformly doped in the perovskite catalyst prepared in Example 1, and lanthanum, manganese and nickel elements are uniformly distributed in the catalyst.
[0063] Comparative Example 1
[0064] This comparative 1 provides a method for preparing an unmodified lanthanum manganese perovskite catalyst (LaMnO3), and the specific steps are as follows:
[0065] Mixing lanthanum nitrate, manganese nitrate and citric acid in a molar ratio of 1:1:2 in a mixture of ethanol and water in a ratio of 3:1 to form a mixed solution;
[0066] The mixed solution was heated and stirred at 80°C until it reached a gel state, and then dried at 100°C for 6 h to obtain a solid precursor;
[0067] The solid precursor was calcined from room temperature to 300°C at a heating rate of 2°C / min, kept warm for 2 h, and then heated to 700°C at a rate of 2°C / min, kept warm for 2 h. After cooling, the unmodified lanthanum manganese perovskite catalyst LaMnO3 was obtained.
[0068] Figure 2a This is a scanning electron microscope image of the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1 of the present disclosure.
[0069] like Figure 2a As shown, the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1 is in a large block shape, has a large number of particles on the surface, and has no obvious pores.
[0070] Comparative Example 2
[0071] This comparative example 2 provides a doping single strategy to improve the lanthanum manganese perovskite catalyst (LaMn 0.7 Ni 0.3 O3) preparation method, the specific steps are as follows:
[0072] Using nickel nitrate as a dopant, lanthanum nitrate, manganese nitrate, nickel nitrate and citric acid in a molar ratio of 1:0.7:0.3:2 are mixed in a 3:1 mixture of ethanol and water to form a mixed solution;
[0073] The mixed solution was heated and stirred at 80°C until it reached a gel state, and then dried at 100°C for 6 h to obtain a solid precursor;
[0074] The solid precursor was calcined and heated from room temperature to 300°C at a heating rate of 2°C / min, kept at this temperature for 2 h, and then continued to be heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2 h, and then cooled to obtain the doped single-strategy improved lanthanum manganese perovskite LaMn 0.7 Ni 0.3 O3.
[0075] Figure 2b This is a scanning electron microscope image of the improved lanthanum manganese perovskite catalyst doped with a single strategy in Comparative Example 2 of the present disclosure.
[0076] like Figure 2b As shown, compared with the unmodified lanthanum manganese perovskite catalyst prepared in Comparative Example 1, the surface particles of the modified lanthanum manganese perovskite catalyst doped with a single strategy in Comparative Example 2 of the present disclosure are finer and have no obvious pores.
[0077] Comparative Example 3
[0078] This comparative example 3 provides a method for preparing a nano-casting single-strategy improved lanthanum manganese perovskite catalyst (LaMnO3-Nano), and the specific steps are as follows:
[0079] Mixing lanthanum nitrate, manganese nitrate and citric acid in a molar ratio of 1:1:2 in a mixture of ethanol and water in a ratio of 3:1 to form a mixed solution;
[0080] Add nano-silicon dioxide to the mixed solution, the mass ratio of nano-silicon dioxide dosage to the theoretical yield of perovskite is 1:1, heat and stir at 80°C until it reaches a gel state, and then dry at 100°C for 6 hours to obtain a solid precursor;
[0081] The solid precursor is calcined, the solid precursor is heated from room temperature to 300°C at a heating rate of 2°C / min, kept at this temperature for 2 hours, and then continued to be heated to 700°C at a heating rate of 2°C / min, kept at this temperature for 2 hours to obtain a calcined product, the calcined product comprising nano-silicon dioxide and nickel-doped lanthanum manganese perovskite;
[0082] The calcined product was added to a 2 mol / L sodium hydroxide solution to etch away the nano-silicon dioxide to form a nano-pore structure. The etching times were 3 times, and each etching time was 3 h. Then, the product was centrifuged and washed 5 times with deionized water, and dried at 80 ° C for 12 h to obtain the nano-casting single-strategy improved lanthanum manganese perovskite catalyst LaMnO3-Nano.
[0083] Figure 2c This is a scanning electron microscope image of the lanthanum manganese perovskite catalyst improved by the nanocasting single strategy in Comparative Example 3 of the present disclosure.
[0084] like Figure 2c As shown, the nanocasting single strategy improved lanthanum manganese perovskite catalyst in Comparative Example 3 of the present disclosure is in block and partial nanosheet form, with obvious pores caused by etching.
[0085] Furthermore, in order to explore the perovskite crystal structure prepared in Example 1 and Comparative Examples 1 to 3, an X-ray diffraction (XRD) test was performed thereon. The specific test process is as follows:
[0086] Take appropriate amounts of the catalysts in Example 1 and Comparative Examples 1 to 3 respectively, place the catalyst powder on a glass slide at room temperature, press until the surface is smooth, and then send it into a powder X-ray diffractometer for Cu Kα (λ = 1.5418Å) radiation at 40 kV and 40 mA.
[0087] Figure 3 It is the X-ray diffraction pattern of the catalyst in Example 1 and Comparative Examples 1-3 of the present disclosure.
[0088] like Figure 3As shown, it can be seen that all four catalysts show characteristic peaks of the hexagonal LaMnO3 structure, proving the success of their material synthesis. In addition, it is observed that the nanocasting and doping dual-strategy improved lanthanum manganese perovskite catalyst in Example 1 and the nanocasting single-strategy improved lanthanum manganese perovskite catalyst in Comparative Example 3 have significantly lower characteristic peak intensities than the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1 and the doped single-strategy improved lanthanum manganese perovskite catalyst in Comparative Example 2, which is attributed to the smaller grain size and larger specific surface area caused by nanocasting.
[0089] Furthermore, in order to explore the oxygen mobility and low-temperature oxidation ability of the perovskite catalysts prepared in Example 1 and Comparative Examples 1 to 3, a hydrogen temperature-programmed reduction (H2-TPR) test was performed on them. The specific test process is as follows:
[0090] First, 50 mg of the catalysts in Example 1 and Comparative Examples 1 to 3 were taken respectively, and the catalysts were pretreated with argon (Ar) at a flow rate of 50 mL / min at a temperature of 200° C. for 2 h. After the pretreatment, the catalysts were cooled to 50° C.
[0091] Then, a H2 / Ar gas flow (total flow rate of 50 ml / min) containing 10% hydrogen (H2) was passed through the sample at a heating rate of 10 °C / min from 50 to 800 °C. The consumption of H2 was continuously recorded using a thermal conductivity detector (TCD).
[0092] Figure 4 It is a comparison chart of hydrogen reduction temperature and consumption of the catalyst in Example 1 of the present disclosure and comparative examples 1 to 3, wherein a is a chart of hydrogen consumption of the catalyst in Example 1 of the present disclosure and comparative examples 1 to 3 as the temperature changes; b is a comparison chart of total hydrogen consumption of the catalyst in Example 1 of the present disclosure and comparative examples 1 to 3 before and after 600°C.
[0093] like Figure 4 As shown, below 600°C, the peak temperatures of the perovskite catalyst LaMnO3 in Comparative Example 1 are 397°C and 487°C, and the consumption of H2 is 0.95 mmol / g; 0.7 Ni 0.3 The peak temperatures of O3 are 375°C and 482°C, the low-temperature oxidation performance is improved to a certain extent, and the consumption of H2 is 0.811 mmol / g; while the peak temperatures of the perovskite catalyst LaMnO3-Nano in Comparative Example 3 are 324°C and 449°C, and the consumption of H2 is significantly increased to 1.193 mmol / g, which is 26% higher than that of the perovskite catalyst in Comparative Example 1. 0.7 Ni 0.3The peak temperature of O3-Nano was further reduced to 178°C, 316°C and 393°C, and the H2 consumption was significantly increased to 2.172 mmol / g, which was 64% higher than that of the catalyst in Comparative Example 1. Therefore, the reduction temperature and H2 consumption of the perovskite catalyst prepared by the dual strategy of nanocasting and element doping were greater than the sum of the improvements of the perovskite catalysts prepared by the two single strategies, further demonstrating the synergistic effect of the two strategies of nanocasting and metal element doping.
[0094] Example 2
[0095] The perovskite catalysts in Example 1 and Comparative Examples 1 to 3 were used to degrade hexachlorobutadiene, and the specific steps were as follows:
[0096] 50 mg of the perovskite catalysts in Example 1 and Comparative Examples 1 to 3 were weighed and placed in glass bottles, and 1.68 μg of hexachlorobutadiene was added to each glass bottle. Then, air with a total flow rate of 30 mL / min and a humidity of 10% was introduced into each glass bottle to simulate the gas conditions in the actual environment. Subsequently, the reaction temperature was raised to 250° C., and a hexachlorobutadiene degradation experiment was carried out.
[0097] The degradation products during the degradation of hexachlorobutadiene by the perovskite catalyst in Example 1 and Comparative Examples 1 to 3 were quantitatively analyzed:
[0098] The exhaust gas produced after degradation was collected using a polytetrafluoroethylene sampling bag (Teflon FEP, 10 L), and 117 volatile organic compounds (VOCs) in the exhaust gas were detected by gas chromatography-mass spectrometry-flame ionization detector / mass spectrometry detector (GC-FID / MS).
[0099] Figure 5 It is a quantitative distribution diagram of degradation products during the degradation of hexachlorobutadiene by the catalyst in Example 1 and Comparative Examples 1 to 3 of the present disclosure.
[0100] like Figure 5As shown, when the catalysts in Example 1 and Comparative Examples 1 to 3 are used to degrade hexachlorobutadiene, only about 17 of the 117 VOCs in the tail gas produced are detected. Compared with the perovskite catalysts in Comparative Examples 1 to 3, the total amount of by-products produced by the perovskite catalyst in Example 1 is significantly reduced, and the generation of chlorinated by-products is less, while the number of harmless alcohol or alkane by-products is relatively increased. It is proved that the perovskite catalyst prepared by the dual strategy of nanocasting and doping in Example 1 has excellent deep oxidation performance, and can effectively convert most of the hexachlorobutadiene into carbon dioxide (CO2) and water, while significantly reducing the generation of other by-products. It is further confirmed that the perovskite catalyst prepared in Example 1 of the present disclosure has strong catalytic oxidation performance and can efficiently degrade hexachlorobutadiene in halogenated organic pollutants.
[0101] The actual catalytic oxidation effects and differences of the perovskite catalysts in the degradation of hexachlorobutadiene in Example 1 and Comparative Examples 1 to 3 were analyzed:
[0102] Figure 6 It is a comparison chart of the carbon dioxide production produced by thermal catalytic oxidation of hexachlorobutadiene by the catalysts in Example 1 of the present disclosure and Comparative Examples 1 to 3 under the same reaction conditions.
[0103] like Figure 6 As shown, with the extension of reaction time, the CO2 production produced by the thermal catalytic oxidation of hexachlorobutadiene by all perovskite catalysts increased. Among them, after 90 minutes of reaction, the CO2 production of the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1 was 74.94 μg, and the CO2 production of the doped single-strategy improved lanthanum manganese perovskite catalyst in Comparative Example 2 was 153.34 μg, which was 105% higher than the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1; the CO2 production of the nanocasting single-strategy improved lanthanum manganese perovskite catalyst in Comparative Example 3 was 442.49 μg, which was 490% higher than the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1. It is worth noting that the CO2 production of the nanocasting and doped dual-strategy improved lanthanum manganese perovskite catalyst in Example 1 was 637.89 μg, which was 751% higher than the unmodified lanthanum manganese perovskite catalyst in Comparative Example 1. The degree of improvement in the actual catalytic oxidation effect of hexachlorobutadiene is greater than the sum of the two single-strategy catalysts in Comparative Examples 2 and 3, indicating that the dual-strategy improved catalyst is far more effective in catalytic oxidation of hexachlorobutadiene than a single improved strategy, showing an obvious synergistic improvement effect.
[0104] Further analysis shows that the catalytic effect of the unmodified lanthanum manganese perovskite on hexachlorobutadiene in Comparative Example 1 is poor, while the nickel doping on the surface of the modified lanthanum manganese perovskite catalyst in Comparative Example 2 can increase the catalytic active sites by causing changes in the electronic structure, promote electron transfer and oxygen activation, and improve the catalytic activity of the catalyst, but the effect is limited. The nanocasting single strategy improved lanthanum manganese perovskite catalyst in Comparative Example 3 shows that the microscopic morphology structure of the catalyst can be improved by nanocasting, and its adsorption capacity and oxidation capacity can be improved, which significantly improves the catalytic activity of the catalyst. However, in the redox cycle of the pollutant catalytic reaction process, a single enhanced oxygen adsorption or oxygen activation cannot form a complete oxidation path improvement, resulting in limited improvement in redox capacity and catalytic effect. The nanocasting and doping dual strategy improved lanthanum manganese perovskite catalyst in Example 1 shows that by effectively combining and regulating the two strategies of nanocasting and element doping, respectively promoting oxygen adsorption and activation, this synergistic effect forms a complete oxidation path improvement, and achieves a catalytic oxidation effect of "1+1>2" on the halogenated organic pollutant hexachlorobutadiene.
[0105] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A method for preparing a nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst, comprising: Using a transition metal salt as a dopant, mixing the transition metal salt, a lanthanum salt, a manganese salt and a complexing agent in a solvent to form a mixed solution; Adding nano-silicon dioxide to the mixed solution, stirring and heating to a gel state, and then drying to obtain a solid precursor; Calcining the solid precursor to obtain a calcined product, wherein the calcined product includes nano-silicon dioxide and transition metal-doped lanthanum manganese perovskite; The calcined product is added into an alkaline solution, and the nano silicon dioxide is etched and removed to form a nano pore structure, thereby obtaining a perovskite catalyst.
2. The preparation method according to claim 1, wherein The transition metal salt, lanthanum salt, and manganese salt are soluble salts selected from any one of nitrates, sulfates, and citrates, wherein the transition metal is selected from any one of iron, cobalt, nickel, and copper; The complexing agent is selected from organic acids, preferably any one of citric acid, ethylenediaminetetraacetic acid, and lactic acid; The solvent is a mixed solution of ethanol and water, with the proportion of ethanol being 0-1, preferably 0.6-0.8; The molar ratio of the lanthanum salt, manganese salt, transition metal salt and complexing agent is 1:(1-x):x:2, wherein the range of x is 0-1, preferably 0.2-0.
4.
3. The preparation method according to claim 1, wherein The nano-silicon dioxide particle size is less than 300 nm. The mass ratio of the nano-silicon dioxide dosage to the theoretical yield of perovskite is 1:2 to 1:1; The heating temperature is 80-95°C, and the drying temperature is 80-120°C.
4. The preparation method according to claim 1, wherein The calcination treatment includes: firstly heating the solid precursor to a first calcination temperature, carrying out a heat preservation reaction, and then continuing to heat the solid precursor to a second calcination temperature for calcination to obtain a calcined product.
5. The preparation method according to claim 4, wherein The first calcination temperature is 200-300°C, the first heating rate is 1-3°C / min, and the holding time is 1-2 h; The second calcination temperature is 700-800°C, the second heating rate is 1-3°C / min, and the calcination time is 1-2 h.
6. The preparation method according to claim 1, wherein The alkaline solution is selected from any one of a sodium hydroxide solution or a potassium hydroxide solution, and the concentration is 1-3 mol / L; The etching times are 3 to 5 times; The etching time is 2 to 4 h each time.
7. A nano-casting and doping dual strategy improved lanthanum manganese perovskite catalyst with nanopore structure and transition metal doping.
8. Use of the nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst according to claim 7 in the degradation of halogenated organic pollutants.
9. The use according to claim 8, wherein: The degradation method comprises: The nano-casting and doping dual-strategy improved lanthanum manganese perovskite catalyst and the halogenated organic pollutant are placed in a reactor, and then air is introduced, and the halogenated organic pollutant is degraded under heating conditions.
10. The use according to claim 9, wherein: The halogenated organic pollutants include any one of hexachlorobutadiene, hexachlorobenzene and chloroform; The heating temperature is 200-350°C; The humidity of the air is 0-20%, and the flow rate is 20-100 ml / min.
Citation Information
Cited By
Gd-doped coupling acid etching modified lanthanum-manganese perovskite and preparation method and application thereof
CN121372396A
Preparation method and application of manganese oxide-based catalyst
CN122298515A
